2015
DOI: 10.1515/cclm-2015-0733
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the commutability of reference material formats for the harmonization of amyloid-β measurements

Abstract: Background: The cerebrospinal fluid (CSF) amyloid-β (Aβ42) peptide is an important biomarker for Alzheimer's disease (AD). Variability in measured Aβ42 concentrations at different laboratories may be overcome by standardization and establishing traceability to a reference system. Candidate certified reference materials (CRMs) are validated herein for this purpose. Methods: Commutability of 16 candidate CRM formats was assessed across five CSF Aβ42 immunoassays and one mass spectrometry (MS) method in a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…Although both platforms are consistent in showing increases in plasma tau levels in patients with AD, the Aβ42 findings were opposite. It has been cautioned that comparing findings between different platforms could be problematic [73, 74]. However, future studies are needed to replicate the differences in findings between platforms before the issue of whether plasma Aβ42 levels are increased or decreased in AD can be resolved.…”
Section: Resultsmentioning
confidence: 99%
“…Although both platforms are consistent in showing increases in plasma tau levels in patients with AD, the Aβ42 findings were opposite. It has been cautioned that comparing findings between different platforms could be problematic [73, 74]. However, future studies are needed to replicate the differences in findings between platforms before the issue of whether plasma Aβ42 levels are increased or decreased in AD can be resolved.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern may suggest that the reanalysed results are a more faithful approximation of amyloid-β 42 levels across groups, the centralized analysis component having removed the variance imposed by differences in INNOTEST measurements between laboratories. While it is thus tempting to speculate that MSD and MS-RMP providing more accurate estimates of amyloid-β 42 concentration levels, this explanation seems unlikely since these analytical techniques have been shown to correlate tightly—both with one another, and with INNOTEST—when samples are analysed in a single run under standardized conditions (Bjerke et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Future studies on amyloid biomarkers, however, should examine the effect of this type of correction. As a further caveat, the INNOTEST amyloid-β 42 ELISA would ideally have been used instead of MSD, though the effect of this is likely to have been minimal (Bjerke et al , 2016). Other possible limitations include the relatively low number of cognitively normal subjects and patients with FTD and VaD, as well as the fact that APOE genotype data was not available for all subjects.…”
Section: Discussionmentioning
confidence: 99%
“…When using algorithms including concentrations of a number of different biomarkers (e.g., synapse proteins, tau, Aβ isoforms) for decision-making, one needs to understand how each individual protein will be affected by changes in (pre-)analytical conditions. For example, Bjerke et al [17] reported that only native CSF without additives is commutable for multiple method comparisons, including mass spectrometry. In addition, the selection of the matrix type for use as a quality control sample in the assay is important [18], while the effect of changes in biomarker concentrations on clinical decision-making must be documented for each analyte [19].…”
Section: Discussionmentioning
confidence: 99%